Evaluating IgG Levels, Vaccination Effects, and COVID-19 Infection Severity in Renal Transplant Recipients - Zana Mohammed; Awny Jafar Ahmed; Majeed Hussein Mustafa; Domiana Shamoon Warda; Masood Ahmed Hameed; Nawfal R. Hussein (QAASPA Publisher, 2024)
Several studies have reported that different factors play an important role in the production of IgG after VOVID-19 vaccination. This study aimed at studying COVID-19 infection rates and severity in renal transplant recipients and vaccine responsiveness. comorbidity hemodialysis requirements, and immune suppression treatment regimens. In this cross-sectional study, IgG levels was measured in renal transplant recipients using automated benchtop immunoanalyzer Vidas at the Duhok Center for Kidney Disease and Transplantation. In this study group, only 30 individuals experienced the SARS-COVID-2 infection, with only three cases being severe. The most frequently reported symptoms of SARS-COVID-2 virus infection were fatigue (18/30) 60%, high temperature (17/30) 56%, headache (12/30) 40%, and poor endurance (11/30) 36.6%. The IgG titers were significantly different between the vaccinated 33.067 ± 2.5 versus unvaccinated individuals 23.916 ± 3.31with p value = 0.025.  On the other hand, demographic characteristics of the cohort including: comorbidities, hemodialysis, different age groups, gender, infection/no-infection differences had no statistically significant impact on the IgG titers.  Vaccination significantly increased the levels of protective IgG level in kidney transplant recipients. It is crucial to focus on increasing the acceptance of vaccination among kidney transplant recipients to prevent infections from other COVID-19 variants or pathogen outbreaks.